2018
DOI: 10.1113/jp276239
|View full text |Cite
|
Sign up to set email alerts
|

Transverse cardiac slicing and optical imaging for analysis of transmural gradients in membrane potential and Ca2+ transients in murine heart

Abstract: Key points A robust cardiac slicing approach was developed for optical mapping of transmural gradients in transmembrane potential (V m) and intracellular Ca2+ transient (CaT) of murine heart.Significant transmural gradients in V m and CaT were observed in the left ventricle.Frequency‐dependent action potentials and CaT alternans were observed in all ventricular regions with rapid pacing, with significantly greater incidence in the endocardium than epicardium.The observations demonstrate the feasibility of our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 53 publications
2
32
0
Order By: Relevance
“…Importantly, a slice thickness of 350 µm is selected to maximize viability while attaining optimal electrophysiological signals. This value is in line with other studies that have reported thicknesses ranging from 150 to 500 µm 11 , 12 , 15 , 37 , with most studies in humans setting it at 300–400 µm 6 , 7 , 11 , 16 , 33 . Also, a post-cutting recovery time of 30 min is applied, consistent with previously reported times for myocardial slices to allow them to attain steady-state properties 6 , 7 , 13 , 15 , 16 , 33 , 37 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Importantly, a slice thickness of 350 µm is selected to maximize viability while attaining optimal electrophysiological signals. This value is in line with other studies that have reported thicknesses ranging from 150 to 500 µm 11 , 12 , 15 , 37 , with most studies in humans setting it at 300–400 µm 6 , 7 , 11 , 16 , 33 . Also, a post-cutting recovery time of 30 min is applied, consistent with previously reported times for myocardial slices to allow them to attain steady-state properties 6 , 7 , 13 , 15 , 16 , 33 , 37 .…”
Section: Discussionsupporting
confidence: 92%
“…www.nature.com/scientificreports/ thicknesses ranging from 150 to 500 µm 11,12,15,37 , with most studies in humans setting it at 300-400 µm 6,7,11,16,33 . Also, a post-cutting recovery time of 30 min is applied, consistent with previously reported times for myocardial slices to allow them to attain steady-state properties 6,7,13,15,16,33,37 . We note that some transmural core biopsies render slices with areas of not totally aligned fibers, accumulation of fibrosis or presence of blood vessels, which may represent a higher percentage of its total volume as compared to other more commonly used myocardial slices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our approach advances these existing models by including a fully functional epicardium, physiologically interfaced to the myocardium. To enable these preparations, we advanced existing embedding methods to protect the epicardial surface whilst achieving a flat cutting surface (27,28). In fact, the epicardium has commonly been used to attach cardiac tissue blocks to specimen holders due to its flatness, which helps to align the tissue, preventing their damage during cutting (29), our methods achieves similar results, without losing the epicardium.…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of The Journal of Physiology , Wen and colleagues () present a novel optical mapping approach using short‐axis tissue slices from the mouse heart that provides for unprecedented, and potentially high‐throughput, characterization of action potentials (APs) and intracellular Ca 2+ transients (CaTs) everywhere in the mouse ventricles. Following dye loading via traditional Langendorff perfusion, the ventricles were embedded in low‐melt agarose and thin (300 μm) short‐axis slices were cut from apex to base, resulting in approximately 20 slices comprising the entire mouse ventricles (akin to a loaf of sliced bread).…”
mentioning
confidence: 99%